Clinicopathological characterization of gall bladder neuroendocrine neoplasm. A case series. - Anupriya, Aarushi; Reshav, Ravi; Fatima, Zikki Hasan; Swarnim Kumar (Student’s Journal of Health Research Africa, 2025)
Background Gallbladder neuroendocrine neoplasms (GB-NENs) are rare, aggressive tumors with limited data on their clinicopathological characteristics. This study aims to evaluate the clinical presentation, radiological features, histopathology, and immunohistochemical (IHC) profile of GB-NENs to enhance diagnostic and therapeutic strategies. Methods A retrospective case series of 15 patients diagnosed with GB-NENs at Homi Bhabha Cancer Hospital and Research Centre over one year was analyzed. Clinical symptoms, radiological findings, tumor markers, histopathology, and IHC markers were reviewed. Results Most patients were female (80%), with a mean age of 56.7 years. Abdominal pain (100%) was the most common symptom, while hepatic invasion (53.3%) was frequently observed on imaging. Histopathology revealed small cell neuroendocrine carcinoma (66.6%), neuroendocrine tumor grade 3 (20%), and mixed neuroendocrine-non-neuroendocrine neoplasm (MiNEN) (13.3%). IHC positivity for PanCK, INSM1, and chromogranin confirmed neuroendocrine differentiation. Conclusion GB-NENs exhibit aggressive behavior with poor prognosis, emphasizing the need for early diagnosis and standardized treatment approaches. Further studies focusing on molecular profiling and targeted therapies are essential for improving patient outcomes. Recommendation Given the rarity and diagnostic complexity of GB-NENs, clinicians should maintain a high index of suspicion in gallbladder masses with atypical imaging or histological features. Routine inclusion of neuroendocrine markers such as INSM1 and chromogranin in gallbladder biopsy evaluations can improve diagnostic accuracy. Multicenter collaborations, molecular characterization, and standardized therapeutic protocols are strongly recommended to enhance patient outcomes and guide future clinical practice.